An evaluation of the status of living collections for plant, environmental, and microbial research - McCluskey, Kevin; Parsons, J. P.; Quach, K.; Duke, C. S. (My University, 2017)
While living collections are critical for biological research, support for these foundational infrastructure elements is inconsistent, which makes quality control, regulatory compliance, and reproducibility difficult. In recent years, the Ecological Society of America has hosted several National Science Foundation–sponsored workshops to explore and enhance the sustainability of biological research infrastructure. At the same time, the United States Culture Collection Network has brought together managers of living collections to foster collaboration and information exchange within a specific living collections community. To assess the sustainability of collections, a survey was distributed to collection scientists whose responses provide a benchmark for evaluating the resiliency of these collections. Among the key observations were that plant collections have larger staffing requirements and that living microbe collections were the most vulnerable to retirements or other disruptions. Many higher plant and vertebrate collections have institutional support and several have endowments. Other collections depend on competitive grant support in an era of intense competition for these resources. Opportunities for synergy among living collections depend upon complementing the natural strong engagement with the research communities that depend on these collections with enhanced information sharing, communication, and collective action to keep them sustainable for the future. External efforts by funding agencies and publishers could reinforce the advantages of having professional management of research resources across every discipline. © 2017 Indian Academy of Sciences
Citation: McCluskey, K., Parsons, J. P., Quach, K., & Duke, C. S. (2017). An evaluation of the status of living collections for plant, environmental, and microbial research. Journal of Biosciences, 42(2), 321-331. https://doi.org/10.1007/s12038-017-9685-6
Keywords: Biodiversity; Genetics; Interdisciplinary Science; Microbiology; Natural Resources; Biology